2021
DOI: 10.1142/s2737416521420059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Polarization on Preformed, β-Strand Rich Homogenous and Heterogeneous Amyloid Oligomers

Abstract: Amyloids are a subset of intrinsically disordered proteins (IDPs) that self-assemble into cross-[Formula: see text] oligomers and fibrils. The structural plasticity of amyloids leads to sampling of metastable, low-molecular-weight oligomers that contribute to cytotoxicity. Of interest are amyloid-[Formula: see text] (A[Formula: see text] and islet amyloid polypeptide (IAPP), which are involved in the pathology of Alzheimer’s disease and Type 2 diabetes mellitus, respectively. In addition to forming homogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…37 Another potential cause for this discrepancy is the limitations of sampling in traditional MD simulations; utilizing advanced sampling techniques such as replica exchange simulations can expand the conformational landscape sampled by modeled peptides. 38 Simulations with the Drude polarizable forcefield on preformed IAPP (20−29) hexamers 39 and IAPP (20−27) fibrils 40 have investigated the stability of parallel and antiparallel aggregates with respect to polarizability. In both studies, parallel structures underwent structural rearrangements; however, parallel morphologies persisted throughout simulation, and structural integrity was preserved.…”
Section: Disruption Of Interpeptide Phe23mentioning
confidence: 99%
“…37 Another potential cause for this discrepancy is the limitations of sampling in traditional MD simulations; utilizing advanced sampling techniques such as replica exchange simulations can expand the conformational landscape sampled by modeled peptides. 38 Simulations with the Drude polarizable forcefield on preformed IAPP (20−29) hexamers 39 and IAPP (20−27) fibrils 40 have investigated the stability of parallel and antiparallel aggregates with respect to polarizability. In both studies, parallel structures underwent structural rearrangements; however, parallel morphologies persisted throughout simulation, and structural integrity was preserved.…”
Section: Disruption Of Interpeptide Phe23mentioning
confidence: 99%
“…It was found that the most stable system was homogenous A-16-22, which gained stability from salt-bridge formation and reduced polarization in hydrophobic residues [ 62 ]. Similarly, another study investigated β-strand rich oligomers with Drude force field and found that structural rearrangement occurred, causing some loss of β-strand structure in favor of random coil content for all oligomers [ 16 ]. It was outlined that low polarization in hydrophobic residues and salt-bridge formation contribute to the stability of homogenous Aβ 16−22 [ 16 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…Short-range interactions, including salt bridges and hydrogen bonds, which are favorable interactions in terms of Coulombic energy, are present inside/among the macromolecules, serving as an important feature contributing to macromolecular architecture. Short-range effects frequently contribute to receptor–ligand binding [ 14 , 15 ] and to the specificity of the binding mode [ 16 , 17 ]. The pH-optimum is the particular pH at which biological activity, macromolecular stability, and binding are best optimized [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of protein polarizable force fields has advanced significantly in the past decade, in particular, the AMOEBA force field based on point-induced dipole , and the Drude force field based on classical Drude oscillator. Polarizable force fields have been used to reveal the importance of polarization effects in modeling salt bridge interactions in proteins, ion binding and selectivity, , helix formation, amyloid aggregation, and protein–ligand binding processes. The recently developed Drude-2019 protein force field has further enhanced the accuracy of protein dynamics through adjustments of the polarizabilities of select C atoms, reoptimized of side chain χ 1 , χ 2 dihedral parameters, and improved description of the interactions between charged residues . To the best of our knowledge, the Drude polarizable force fields have not been applied to study peptide nanotube systems.…”
Section: Introductionmentioning
confidence: 99%